2013
DOI: 10.3109/09273948.2013.791925
|View full text |Cite|
|
Sign up to set email alerts
|

Transplantation of CX3CL1-expressing Mesenchymal Stem Cells Provides Neuroprotective and Immunomodulatory Effects in a Rat Model of Retinal Degeneration

Abstract: CX3CL1-MSCs subretinal transplantation may enhance protective effect against light-induced retinal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In this sense, under oxidative and ischemia/reperfusion conditions and in the absence of CX3CR1, uncontrolled retinal inflammation results in extensive retinal degeneration , and it has been suggested that CX3CL1 can exert a protective effect on the lightinjured retina (Huang et al, 2013a). On the other hand, the expression of fractalkine was found to be significantly upregulated after exposure to light, and was located mainly at the photoreceptors (Zhang et al, 2012a).…”
Section: Microglia In Degenerating Diseasesmentioning
confidence: 98%
“…In this sense, under oxidative and ischemia/reperfusion conditions and in the absence of CX3CR1, uncontrolled retinal inflammation results in extensive retinal degeneration , and it has been suggested that CX3CL1 can exert a protective effect on the lightinjured retina (Huang et al, 2013a). On the other hand, the expression of fractalkine was found to be significantly upregulated after exposure to light, and was located mainly at the photoreceptors (Zhang et al, 2012a).…”
Section: Microglia In Degenerating Diseasesmentioning
confidence: 98%
“…111,112 This has also been accomplished by altering MSC gene expression prior to transplantation. 113,114 …”
Section: Therapeutic Potential Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Very recent data show, however, protective effects of the fractalkine protein on retinal structure and function. This is supported by the analysis of light-injured rat retinas with transplanted mesenchymal stem cells engineered to secrete CX3CL1 [76]. Here the CX3CL1-expressing mesenchymal stem cells inhibited apoptosis of the retinal cells and microglial activation.…”
Section: Discussionmentioning
confidence: 83%